Pharmacotherapy variability and precision medicine in neurocritical care - Sherif Hanafy Mahmoud; Maged Kharouba; Asma Aboelezz; Adham Elshamy; Ellen Gunn (Frontiers in Neurology)
Pharmacotherapy variability is defined as the variability in drug response among and within individuals that is attributed to the inter and intra-individual differences in the action and disposition of drugs. Neurological and medical complications in neurocritical care contribute significantly to the overall disease prognosis. Pharmacological management plays a key role in managing many of those complications such as cerebral vasospasm, delayed cerebral ischemia, hyponatremia, infections, and seizures. However, pathophysiologic changes secondary to neurological and critical illnesses make the medical management of these patients challenging, contributing to pharmacotherapy variability. Interindividual differences in disease pathophysiology, altered organ function, systemic inflammation, hemodynamic instability, and common interventions employed in intensive care settings could alter the pharmacokinetics and pharmacodynamics of medications. The use of potentially ineffective treatments and suboptimal dosing of medications to manage patients can lead to poor outcomes as the understanding of the effect of neurological injury on the action and disposition of drugs is limited. This narrative review highlights the factors contributing to pharmacotherapy variability in neurocritical care, equipping clinicians with critical insights to refine patient management strategies. In conclusion, pharmacotherapy variability within neurocritical care introduces additional layers of complexity that may significantly contribute to therapy failure, adverse drug reactions, and setbacks in drug development. Understanding these variations is essential for identifying subpopulations that may derive the greatest benefit from specific therapies, representing a critical step toward achieving precision medicine in neurocritical care, ensuring the administration of the appropriate medication to the right patient at the correct dosage regimen.